Primary Prevention of Cardiovascular Disease with Collaborative Diabetes Study in the Efficacy of Statins: Meta-Analysis of Randomized Controlled Trials - Hong, Jiang; Iftikhar, Hassah Batool (Cardiology and Cardiovascular Medicine, 2018)
Context: A recent meta-analysis demonstrated the use of statin therapy in an association of ischemic conditioning of high-risk T2DM development. Objective: The purpose of this research is to investigate the effectiveness of statin therapy in metabolic cardiovascular syndrome and mortality by meta-analyses of longitudinal studies. Data sources: We identified relevant trials in a literature search of PUBMED, MEDLINE, EMBASE and Cochrane Central Register from 1994-2013 obtaining the unpublished data to exist the useful finding of statin therapy. Study selection: We included the randomized controlled end points by checking the reference lists of previous systematic reviews conducted on1000 participants per year updated on April 2018 with the clinical follow up of least treatment and titrating dosing issues in measuring the risk ratio of restricted events with the random effect of meta-analysis. Data extraction: The selected studies for inclusion describe the characteristics of T2DM incidence experiencing the outcomes of fatal/nonfatal myocardial Infarction, stroke, left ventricular ejection fraction, glycated hemoglobin, hypertension history and changes in LDL-C and TOT-C the all-cause mortality changes in the quality life. We observed the specific relative risk and mean difference in the combined random effects of statistic heterogeneity assessment. We also contacted the trial authors to obtain the missing data. Results: In 29 study trials with the participants of 3000 developed diabetes representing the additional cardiovascular events groups per 1000 patients yearly experience (3135-3165) respectively with an over-weighted mean STD follow up of 5 years (IV Random 0.43; Confidence Interval -0.88, 1.75 I2=97%) and T2DM on receiving intensive-dosing (IV Random 0.29; Confidence Interval -4.64,